Kedewasaan Beragama Pada Anak Usia Dasar - Mar'atus Sholihah (FALASIFA : Jurnal Studi Keislaman, 2018)
ABSTRACT Mature religion on children who are in elementary or primary phase plays an important rule for their psychology development. This paper found out in theory that children have the ability to recognize what is called â€œreligionâ€ in their heart through their mind by having imagination and thinking logically. The needs of having religion for children are constracted internally by themselves and externally by their nvironment, family and culture. Children develop their religion maturity by three stages based on their age. It is started from age 0-12 year old which explains different development they have. Those stage of developments are related with their ability to be critical and with three kind of intellengences (IQ-SQ-EQ). Keywords: Mature Religion, Children, Development